The impact of COVID-19 on Tunisia’s economy, agri-food system, and households - ElKadhi, Zouhair; Elsabbagh, Dalia; Frija, Aymen; Lakoud, Thouraya; Wiebelt, Manfred; Breisinger, Clemens (International Food Policy Research Institute, 2020)
The COVID-19 crisis is expected to lead to a 46.4 percent decline in Tunisia’s GDP during the 2nd quarter of 2020 (April to June). The industrial sector will be hit hardest, with output falling by 52.7 percent, followed closely by services (-49.0 percent) and agriculture (-16.2 percent). These high losses are a result of the complete lockdown imposed in the country to contain the pandemic. Higher-income urban households will see the largest income losses, although lower-income urban households also will experience significant reductions in their income. As a policy response, social transfers towards poorer households will reduce the adverse welfare impact of these drops in household income. Government policies to support struggling businesses will allow economic activities to revive more rapidly when the lockdown loosens. Consequently, comprehensive planning by the Government of Tunisia to re-open the economy will be critical to reduce the pandemic’s adverse impact on the country’s economy in the longer-term, reducing losses of employment and income, especially in manufacturing and retail.